2011
DOI: 10.1142/s0129065711002717
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Seizure Control With Very High Frequency Electrical Stimulation at Seizure Onset in the Gaers Model of Absence Epilepsy

Abstract: A closed-loop system for the automated detection and control of epileptic seizures was created and tested in three Genetic Absence Epilepsy Rats from Strasbourg (GAERS) rats. In this preliminary study, a set of four EEG features were used to detect seizures and three different electrical stimulation strategies (standard (130 Hz), very high (500 Hz) and ultra high (1000 Hz)) were delivered to terminate seizures. Seizure durations were significantly shorter with all three stimulation strategies when compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 47 publications
1
23
0
1
Order By: Relevance
“…1 While modern imaging techniques are unable to detect the histological features of AD, EEG remains a powerful tool providing high temporal and spatial resolution to study functional connections within different areas of the brain. [2][3][4][5][6][7][8][9][10][11][12] EEG signals are commonly decomposed into subbands: delta (0-4 Hz), theta (4)(5)(6)(7)(8), alpha (8 to 12 Hz), and beta (12 to 30 Hz). Each of the subbands relates to different functional and physiological parts of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…1 While modern imaging techniques are unable to detect the histological features of AD, EEG remains a powerful tool providing high temporal and spatial resolution to study functional connections within different areas of the brain. [2][3][4][5][6][7][8][9][10][11][12] EEG signals are commonly decomposed into subbands: delta (0-4 Hz), theta (4)(5)(6)(7)(8), alpha (8 to 12 Hz), and beta (12 to 30 Hz). Each of the subbands relates to different functional and physiological parts of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Nelson et al 2011 developed an SWD detection system in GAERS based on time-series analysis, gauging changes in amplitude and/or frequency [14] . This system only allowed the detection of the start of the SWD in order to trigger therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This requires use of closed-loop seizure-detection systems, in which seizures are recorded in real time and light is delivered in response to seizures. Closed-loop seizuredetection systems have been used to respond to seizures in real time with electrical stimulation, but such techniques cannot specifically target microcircuits and instead affect many cell types as well as neighboring areas of the brain (Osorio et al 2005;Liang et al 2011;Nelson et al 2011;Berényi et al 2012). With optogenetics, however, recent studies revealed that closed-loop optogenetic intervention can significantly stop seizures in rodent models of epilepsy by targeting appropriate local or even long-range connections to the seizure focus Paz et al 2013).…”
Section: Optogenetic Targeting Of Specific Circuits In Epilepsy Applimentioning
confidence: 99%